Indskriften paa oddens mindestøtte - Albeck, Gustav (Grundtvig-studier, 1948)
The Inscription on the Monument at Sællands Odde. By Gustav Albeck. An article by Sigurd Muller in “ Tidsskrift” (1908) refers to this inscription as an early example of Grundtvig’s unsurpassed mastery of artistic form when at his best. Its perfection may be either due to the unrevised inspiration of a moment, or the fruit of careful work no less than of genius. Muller inclines to the latter explanation; and this is confirmed by the evidence of a rough copy of the poem. A detailed comparison of this and the final version shows that while the former gives us the theme of the poem, it is only in the latter that this theme finds its fitting realisation. In the rough copy the description of the battle and the praise of the dead are intermixed; but in the final version the first verse, full of movement and action, tells of the battle, while in the second verse there is a change from the third to the first person, and a marked change of rhythm, as the memorial stone speaks the praises of the dead; and it is this which gives the poem its artistic effect. A line-by-line comparison of the two versions shows that both refer to the waves being reddened by blood (a similar reference occurs in Grundtvig’s first poem to Willemoes, 1808, and in a poem by Haste on the Battle of Copenhagen, 1801); but in the final version “ Og Bolgerne giordes saa rode” (And the waves were made so red) the vowel sounds convey the picture of the empurpled water much better than in the earlier draft. Both versions begin with “ De Snekker modtes” (The caravels met) — a strong phrase which illustrates Grundtvig’s power of conveying his readers at once into the midst of a situation or a mood. Other lines vividly picture the twilit background of the seafight and the flames of battle in the foreground. The somewhat hackneyed wording of the tribute to the dead in the rough draft disappears in the final version; and instead, in concise and inspired phrases, the second verse declares the fallen to be worthy of remembrance because they were true Danes. Ewald in his “ The Fishers” (1778) had already made “ dansk” a term of praise; and the virtues of the Danish fishers which he extolled found fuller expression in the naval battles in which Danish seamen took part. Grundt107 vig casts a new poetic light upon this extension of the idea of “ Danishness” , filling it, as was his nature, with the past and with the future. The “ speech” of the memorial stone recalls the famous inscription at Thermopylae, which we know was familiar and dear to Grundtvig. In his poem Denmark has her own Thermopylae inscription, combining classic style with the prophetic tones of a new age. Grundtvig himself was conscious that it was a fine artistic creation; this is clear from the Appendix to his “ Kvadlinger” (1815), in which, however, he says that its chief fault was that it made no mention of God. This criticism illustrates the conflict in Grundtvig between the poet and the champion of Christianity, which broke forth with such force in the crisis of his conversion in 1810; but there is plenty of evidence in his other poems, too, that his zeal for proclaiming Christianity did not cause him to neglect the problems of artistic form.